Low-temperature synthesis and characterization of lead-free BaTi0.89Sn0.11O3 piezoelectric powders. (2022) - Zahid, Marwa; Kharraz, Ouissal; Amjoud, M'barek; Mezzane, Daoud; Gouné, Mohamed; Hoummada, Khalid; Saadoune, Ismael; Fourcade, Sebastien; Stocker, Pierre; Rožič, Brigita; Kutnjak, Zdravko; El Marssi, Mimoun
Abstract: Barium stannate titanate (BaTi0.89 Sn0.11 O3, BTS11 ) is one of the reported lead-free materials that exhibit high dielectric and piezoelectric properties near ambient temperature. In this work, BTS11 powders were elaborated via a soft chemistry method at very low temperatures using two synthesized approaches combining sol-gel and hydrothermal processes. In the first approach, the effect of the barium precursor on the purity and the crystallinity of the BTS11 powders were studied. In contrast, in the second approach, the influence of the hydrothermal temperature on the BTS11 proprieties was analyzed. As a result, pure and uniform fine powders were obtained at 180 °C. The appropriate mass fraction of BTS11, which leads to high suspension stability in water, is below 3%. These eco-friendly and pure piezoelectric powders can be used without further heat-treatment in several applications such as lead-free piezoelectric decontamination of organic pollutants and photocatalyst, hydrogen generation and as fillers in flexible nanocomposites nano-generators for energy harvesting and energy storage.